PENGARUH DPK, CAR, NPF, DAN SWBI TERHADAP PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH TAHUN 2008-2012 - WARDIANTIKA, LIFSTIN (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This research has done to know the influence of DPK, CAR, NPF, and SWBI with murabahah financing to syariah bank during 2008-2012. Dependent variable of this research is third party fund (DPK), capital adequacy ratio (CAR), non performing financing (NPF), and Indonesia bank wadiah certificate (SWBI). This research sample is financial report during three month of public syariah bank during 2008-2012. It uses saturated sample method. The data is using secondary data that get from financial report that published by Indonesia Bank. Analysis data method is using multiple linier regression. Analysis result is showing that variable simoultantly DPK, CAR, NPF, and SWBI get influence to murabahah financing. Partially DPK has positive influence to murabahah financing. NPF get negative influence to murabahah financing. While CAR and SWBI hasn’t influence to murabahah financing. Variable explaining independent variable is get 92% while the rest 8% can influenced by other variable. Keywords: Murabahah financing, third party fund (DPK), capital adequacy ratio (CAR), non performing financing (NPF), and Indonesia Bank Wadiah Certificate (SWBI).